Growth performance and quality of Andrographis paniculata in response to organic soil amendment - Zainal, Mohd Zahir (2015)
Andrographis paniculata or King of bitters is known for its extremely bitter taste and its medicinal value. It is commonly used for medicinal purposes and offers relief from an array of ailments. On the other hand, the basic purpose of organic soil amendment is to improve soil chemical and physical properties. The objective of this study was to investigate the effect of types and rates of soil amendment on growth and quality of A. paniculata. Two types of soil amendment namely biochar and chicken manure with the application rate of 0 (control), 5, 10 and 15 ton/ha were used. The experiment was laid out in a Randomized Complete Block Design (RCBD) with four replications. Analysis of variance indicated that there were significant differences (P < 0.05) among the treatments in plant height, total leaf area, fresh weight and dry weight. At 15 ton/ha, both biochar and chicken manure produced higher biomass and yield compared to lower rates of soil amendment and control. Antioxidant activity, total flavonoid and phenolics were also significantly different among the treatments.